2021
DOI: 10.1002/brb3.2070
|View full text |Cite
|
Sign up to set email alerts
|

The stimulus control of local enclosures and barriers over head direction and place cell spatial firing

Abstract: Objective Head direction cell and place cell spatially tuned firing is often anchored to salient visual landmarks on the periphery of a recording environment. What is less well understood is whether structural features of an environment, such as orientation of a maze sub‐compartment or a polarizing barrier, can likewise control spatial firing. Method We recorded from 54 head direction cells in the medial entorhinal cortex and subicular region of male Lister Hooded rats while they explored an apparatus with fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…This observation was then extended to two-compartment environments in which rats could walk under their own volition from one compartment to another [ 16 ] ( figure 4 b ), where it was found that firing directions would be aligned provided the second environment was novel when the rat did so (see also [ 17 ]). Firing directions of classic head direction cells also remain aligned across two connected compartments even if the visual scenes are rotated with respect to each other [ 18 , 19 ] (but see below for non-classic directional cells). Thus, it seems that self-motion cues can be used to coordinate the signals across the two spaces: something that may be adaptive for navigation.…”
Section: Spatial Symmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was then extended to two-compartment environments in which rats could walk under their own volition from one compartment to another [ 16 ] ( figure 4 b ), where it was found that firing directions would be aligned provided the second environment was novel when the rat did so (see also [ 17 ]). Firing directions of classic head direction cells also remain aligned across two connected compartments even if the visual scenes are rotated with respect to each other [ 18 , 19 ] (but see below for non-classic directional cells). Thus, it seems that self-motion cues can be used to coordinate the signals across the two spaces: something that may be adaptive for navigation.…”
Section: Spatial Symmetriesmentioning
confidence: 99%
“…This dissociation between translation and rotation might be explained by the dissociable routes in to the system of directional information (via the head direction system) versus linear motion information (the source of which is still not identified). These two information sources, which we assume to be responsible for the rotational and translational symmetry respectively, can be placed in conflict if the local environment is rotated with respect to the global, room environment: in this situation grid cells rotate their grids somewhat [ 46 ], and it seems head direction cells may also do so as well, although very subtly [ 18 ], indicating that both global and local cues can contribute to directional calculations.
Figure 5 Symmetry-breaking in grid cells.
…”
Section: Spatial Symmetriesmentioning
confidence: 99%